STRATEGI KEUANGAN MATRIKS: ALAT BANTU KEPUTUSAN INVESTASI DAN PEMBIAYAAN PADA PERBANKAN SYARIAH DI INDONESIA - Hafidzi, Achmad Hasan; Zulkarnaeni, Achmad Syahfrudin; Megayani, Nurhayati; Herlina, Nita (BISMA: Jurnal Bisnis dan Manajemen, 2020)
This study analyzes Islamic commercial banks' financial conditions using a matrix financial strategy, with its growth, investment decisions, and financing approach. The measuring instruments used are ROIC, WACC, and EVA. This research sample was 12 Islamic commercial banks in Indonesia, taken by using the purposive sampling technique. The results showed that 7 Islamic commercial banks were in quadrant three, i.e., BRI Syariah, BNI Syariah, Bank Syariah Mandiri, Bank Syariah Mega Indonesia, and Bank Panin Syariah. Then, there were four sharia commercial banks in quadrant two, namely Bank Syariah Bukopin, BCA Syariah, Maybank Syariah, and BTPN Syariah. There was one sharia commercial bank in quadrant 1, namely Bank Muamalat. Using a matrix financial strategy, Islamic commercial banks can develop strategies that lead to the effectiveness of investment decisions and financing decisions. Keywords : EVA, matrix financial strategy, ROIC, WACC